A new bis-labdanic diterpene from the rhizomes of Alpinia pahangensis - Sivasothy, Y.; Ibrahim, H.; Paliany, A.S.; Alias, S.A.; Md Nor, N.R.; Awang, Khalijah (Georg Thieme Verlag, 2013)
The rhizomes of Alpinia pahangensis yielded a new bis-labdanic diterpene for which the name pahangensin C (1) was proposed along with twelve known analogues (2–13). The structure of 1 was elucidated via spectroscopic methods including 1D and 2D NMR techniques and LCMS‑IT‑TOF analysis. Compounds 2 and 12 were isolated for the first time from the genus Alpinia. This is the second occurrence of compounds 2 and 12 in the Zingiberaceae family. Selected analogues exhibited moderate to strong inhibitory activity against Staphylococcus aureus and Bacillus cereus.